Stress and Coping with Discrimination and Stigmatization - Berjot, Sophie; Gillet, Nicolas (Frontiers in Psychology, 2011)
The aim of this article is to briefly review the literature on stigmatization and more generally identity threats, to focus more specifically of the way people appraise and cope with those threatening situations. Based on the transactional model of stress and coping (Lazarus and Folkman, 1984), we propose a model of coping with identity threats that takes into accounts the principle characteristic of stigma, its devaluing aspect. We present a model with specific antecedents, a refined appraisal phase and a new classification of coping strategies based on the motives that may be elicited by the threatening situation, those of protecting and/or enhancing the personal and/or social identity.